The Contribution Nonformal Education in Tourism Development Through Empowerment and Training of Street Vendors - Ariefianto, Lutfi; Hilmi, Muhammad Irfan (Journal of Nonformal Education, 2019)
Jember Regency has a Malikan White Sand Beach tourist attraction known as "PAPUMA" which is a destination for both local and foreign tourists. Tourists, one of which is a street vendor around tourist attractions has a very important role in the effort to develop tourist attractions so that they become the "icon" of a famous area. The existence of street vendors around the coast of the coast needs to be empowered and fostered so that tourism development business becomes the joint responsibility of coastal communities, tourism actors and tourists. This study aims to determine the contribution of Nonformal Education as an alternative education in empowering and fostering street vendors in coastal communities "PAPUMA" in Jember Regency. This study uses a qualitative approach. Data collection uses in-depth interview techniques, observation and documentation. The results of the study show that Nonformal Education contributes through its excellent programs such as Information (through community awareness movements, social motivation). The outreach agenda that has been given is the launch of awareness of local potential, hygiene and health counseling, counseling about the importance of preserving nature so that nature can protect humans. Institution through training provided to street vendors to provide new skills to them, such as business management skills, business presentations so that their business increases.